RANCANG BANGUN KENDALI OTOMATIS LAMPU DAN PENDINGIN RUANGAN PADA RUANG PERKULIAHAN BERBASIS MIKROKONTROLER ARDUINO NANO - Yoga Widiana, I Wayan; Raka Agung, I Gusti Agung Putu; Rahardjo, Pratolo (Jurnal SPEKTRUM; Vol 6 No 2 (2019): Jurnal SPEKTRUM, 2019)
Automatic control technology for energy savings is no stranger to social life. Negligence in turning off lights and air conditioners in class is one example of the waste of electricity that occurs in school and campus institutions. By using the PIR (Passive Infra Red) sensor and LDR (Light Dependent Resistor) on the automatic control system of lights and air conditioners, it is expected to reduce excess electricity consumption. All uses of sensors are connected directly to Arduino Nano as the center of automatic system controllers. Software design uses the basic programming language C Arduino and utilizes the timer library function which functions as a room timer. From the results of the research, this tool can already be used as an automation while saving electricity consumption in the use of electronic devices such as lights and air conditioners.